Diseño de unidades didácticas en el área de Ciencias Experimentales - Sánchez Blanco, Gaspar; Valcárcel Pérez, María Victoria (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
This study puts forward some planning strategies for the teaching of Science based on a constructivist approach for the teaching/learning process. These strategies are shown in a model for the design of teaching units which includes five interdependent tasks: scientific analysis, pedagogical analysis, selection of objectives, selection of pedagogical strategies and selection of evaluation strategies. The first two aim at the reflection and estimation of contents and constrains of the teaching/learning processes. The other three are concerned with teachers' decision making and the explicitness of their teaching plans, as well as with their classroom performance in order to achieve them.